An Overview of an Acidic Uranium Mine Pit Lake (Caldas, Brazil): Composition of the Zooplankton Community and Limnochemical Aspects - Ferrari, Carla R.; Azevedo, Heliana de; Wisniewski, Maria Jose S.; Rodgher, Suzelei [UNESP]; Roque, Claudio Vitor; Nascimento, Marcos Roberto L. (Springer, 2015)
Water samples were collected quarterly for 1 year from the newly created Osamu Utsumi uranium mine pit lake, Brazil, which is affected by acid mine drainage (AMD). The water presented mean pH values of 3.8, high mean electrical conductivity values (2391 A mu S/cm), manganese (74 mg/L), sulfate (1413 mg/L) and uranium (3 mg/L). The density of rotifera was significantly higher than that of cladoceran. Rotifera Keratella americana, K. cochlearis and the Cladocera Bosminopsis deitersi, Bosmina sp., are being reported for the first time in samples from a uranium pit lake with AMD. Of the species registered, the order Bdelloidea was the most important in terms of density (17,500-77,778 ind/m(3)), since it occurred throughout the whole sampling period. The combined effect of moderately acidic pH and other potential stress factors, such as high concentrations of stable and radioactive contaminants, probably influenced the zooplankton species composition in the pit lake.
Keywords: Mine pit lake; Acid mine drainage; Bdelloidea